Partial discharge characteristics of low-density polyethylene and effect of nanofiller using pulse sequence analysis - Arief, Yanuar Zulardiansyah (SHIBAURA INSTITUTE OF TECHNOLOGY, 2016)
This paper describes the partial discharge (PD) characteristics in leaf-like type of low-density polyethylene (LDPE) with nano-Magnesium Oxide (MgO) samples which were investigated using the pulse sequence analysis (PSA) method. This method enables to evaluate the individual sequences of PD events in data sets instead of just accumulated data sets as commonly used in investigations of PD characteristics with the conventional methods. The nano-MgO filler amount was 0, 1, 5, and 10%, respectively. The samples were loaded with a ramped AC-voltage 1.14 kVrms/min up to 4096 PD pulses had occurred. The sensitivity was set about 16 pC. The results revealed that the discharge characteristics change during the growth of an electrical tree depending on sample types and filler amount.